Oxymatrine inhibits proliferation of human bladder cancer T24 cells by inducing apoptosis and cell cycle arrest - Li, Shun (Oncol Lett, 2017)
Oxymatrine has been shown to exert an antitumor effect on several types of cancer cells. However, the role of oxymatrine in bladder cancer has not yet been evaluated. The present study was designed to investigate the potential anti-proliferative effect of oxymatrine on bladder cancer T24 cells and the possible mechanisms involved. A 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay was used to determine cell growth, and the cell morphology was examined using hematoxylin and eosin staining, wrights' staining and electron microscopy. The caspase-3 and survivin mRNA and protein levels were assessed using reverse transcription-quantitative polymerase chain reaction and western blot analysis, respectively. The expression of tumor protein p53 (p53), Bcl-2-associated X protein (Bax) and B-cell lymphoma 2 (Bcl-2) were analyzed using immunohistochemistry. Oxymatrine inhibited the proliferation of the T24 cells in a dose- and time-dependent manner. Oxymatrine also induced apoptosis and cell cycle arrest in the cells, in association with the upregulation of caspase-3 and Bax, and the downregulation of survivin, Bcl-2 and p53 expression. Overall, oxymatrine inhibits the proliferation of human bladder cancer cells by inducing apoptosis and cell cycle arrest via mechanisms that involve p53-Bax signaling and the downregulation of survivin expression.